Overview of MitoQ on prevention and management of cardiometabolic diseases: a scoping review - Pang, Mingli; Wang, Shidi; Shi, Tianyi; Chen, Jinsong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe exploration of mitochondrial-targeted antioxidants represented a burgeoning field of research with significant implications for cardiometabolic diseases (CMD). The studies reviewed in this scoping analysis collectively highlighted the effect of MitoQ on prevention and management of CMD and underlying mechanisms were discussed, mainly including cardiovascular diseases (CVDs), liver health and others.MethodsThis scoping review aimed to synthesize current research on the health impacts of MitoQ on CMD, focusing primarily on human-based clinical trials. While the primary focus was on human trials, in vivo and in vitro studies were referenced as supplementary material to provide a broader understanding of MitoQ's mechanisms and potential effects.ResultsThis scoping review had synthesized the findings that collectively contributed to the understanding of mitochondrial-targeted antioxidants and their role in CMD.ConclusionThe synthesis of these findings illustrated a broad spectrum of benefits ranging from enhanced insulin secretion to improved lipid profiles and mitochondrial function, yet the path to clinical application required further investigation on appropriate doses and populations.